The role of agriculture and agro-processing for development in Tunisia - Figueroa, Jose Luis; Mahmoud, Mai; El-Enbaby, Hoda (International Food Policy Research Institute, 2018)
This paper is part of a series of three country-case studies to investigate the potential role of agro-processing for economic development based on the strong backward and forward linkages agro-processing firms have with the agricultural sector. Previous analyses for Egypt and Jordan (Figueroa, Mahmoud, and Breisinger 2017; El-Enbaby et al. 2016) have shown how developing the agro-processing sub-sector as well as encouraging the production of high-value crops can promote economic and social well-being, especially in rural areas where the majority of the poor are concentrated. In continuation with this line of research, this paper aims at analyzing: • What role agriculture has played for the Tunisian economy in recent years; • What is the role of agricultural productivity and structural change in fostering agricultural growth in Tunisia; and • What is the potential of agro-processing for economic development and rural transformation in the country.